Triphala Churna—A Traditional Formulation in Ayurveda Mitigates Diabetic Neuropathy in Rats - Suryavanshi, Sachin V.; Barve, Kalyani; Addepalli, Veeranjaneyulu; Utpat, Sachin V.; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2021)
Neuropathy is a common complication of diabetes affecting large number of people worldwide. Triphala churna is a formulation mentioned in Ayurveda- a traditional system of medicine. It is a simple powder formulation consisting of powders of three fruits, Emblica officinalis, Terminalia bellerica and Terminalia chebula. Individual components of Triphala churna have anti-diabetic and antioxidant activities. Hence, this study was designed to evaluate effect of Triphala churna in diabetic neuropathy. Diabetes was induced with streptozotocin (55 mg/kg, i.p.) in rats. Six weeks after induction of diabetes, animals were treated with Triphala churna at dose of 250, 500 and 1000 mg/kg, for 4 weeks. At the end of study, parameters such as body weight, plasma glucose level, motor nerve conduction velocity were determined. The effect of Triphala churna on thermal hyperalgesia, mechanical hyperalgesia, and mechanical allodynia was also determined at the end of study. The plasma cytokine levels like TGF-β1, TNF-α, and IL-1β were determined by ELISA assay. Histopathology study of sciatic nerve was studied. Western blotting was performed to study expression of Neuronal growth factor. Treatment with Triphala churna showed significant reduction in plasma glucose, and significant rise in body weight. Triphala treatment significantly increased the motor nerve conduction velocity and decreased the thermal and mechanical hyperalgesia, as well as mechanical allodynia. The treatment significantly inhibited levels of circulatory cytokines like TGF-β1, TNF-α, and IL-1β. Histopathology study confirmed the neuroprotective effect of Triphala churna. The expression of NGF was significantly increased in sciatic nerves after treatment with Triphala churna. From the results it can be concluded that Triphala churna delays the progression of neuropathy in diabetic rats.